2015
DOI: 10.5897/ajar2014.9192
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of livelihood diversification strategies: The case of smallholder rural farm households in Debre Elias Woreda, East Gojjam Zone, Ethiopia

Abstract: Smallholder rural farm households face an increasing need of looking for alternative income sources to supplement their small scale agricultural activities. However, livelihood diversification is determined by complex and yet empirically untested factors in Debre Elias Woreda. Thus, the aim of this study is to assess the determinants of livelihood diversification strategies in the study area. The data were collected through both primary and secondary data collection methods. The data were obtained from 160 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 4 publications
9
53
2
Order By: Relevance
“…The possible reason can be a smaller amount of cultivated land is not enough to the households to make a sufficient living from farm production alone, causing them to work for supplementary non/off farm income generating activities. This finding is in agreement with that of Yenesew et al, (2015).…”
Section: Determinants Of Livelihood Diversification Strategiessupporting
confidence: 83%
See 1 more Smart Citation
“…The possible reason can be a smaller amount of cultivated land is not enough to the households to make a sufficient living from farm production alone, causing them to work for supplementary non/off farm income generating activities. This finding is in agreement with that of Yenesew et al, (2015).…”
Section: Determinants Of Livelihood Diversification Strategiessupporting
confidence: 83%
“…Contrary to this result, Yenesew et al, (2015) found negative correlation between market distance and livelihood diversification. Credit facilities (CREDCOST): As expected, access to formal credit was found to have a positive effect on the level of livelihood diversification at 1 percent level of significance.…”
Section: Determinants Of Livelihood Diversification Strategiescontrasting
confidence: 54%
“…In Ethiopia, most of the studies conducted identify three rural livelihood diversification strategies: on farm, nonfarm and off farm (Mengistie and Kidane, 2016;Debele and Desta, 2016;Gecho, 2017;Kassie et al, 2017;Teklu et al, 2017;Yona and Mathewos, 2017;Ofolsha and Mansingh, 2015;Dadi, 2016;Asfir, 2016;Addisu, 2017;Yizengaw et al, 2015). Authors mention crop production and livestock rearing as major activities of on farm livelihood activities.…”
Section: Rural Livelihood Diversification Strategies In Ethiopiamentioning
confidence: 99%
“…Currently, there is a growing evidence that rural households in rural Ethiopia are participated in diverse livelihood strategies away from purely crop and livestock production towards non-farm and off-farm activities that are undertaken to broaden and generate additional income for survival and cope with different livelihood shocks, trends, and seasonality associated with agricultural production [6][7][8]. However, their participation is determined by various contextual factors such as Agro-ecology, educational level of the household, land size, livestock ownership, total income, family size, access to credit service, remittance receiving, dependency ratio [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Though there are many livelihood studies done in the world and Ethiopia, few scientific works [11][12][13], had been done in Amhara region in relation to factors that could influence the choice of livelihood diversification strategies and they were not able to give enough information on exiting livelihood strategies and its determinant. This could be due to the disparity in the effect of factors affecting livelihood diversification strategies at different locations with different livelihood outcomes [12].…”
Section: Introductionmentioning
confidence: 99%